Microstructure and Mechanical Properties of Zinc Matrix Biodegradable Composites Reinforced by Graphene - Dai, Qianfei; Peng, Shanshan; Zhang, Zongkui; Liu, Yuan; Fan, Mei; Zhao, Fei (Frontiers in Bioengineering and Biotechnology, 2021)
This work used spark plasma sintering (SPS) to prepare graphene nanosheets（GNS）reinforced zinc matrix composites. The influence of GNS on the microstructure and mechanical properties of zinc matrix composites was studied. The results show that the GNS/Zn composites prepared by spark plasma sintering have a dense structure and good interface bonding, and GNS are uniformly distributed in the zinc matrix. Adding GNS can significantly improve the mechanical properties of the zinc matrix. When 0.7 wt% GNS are added, the comprehensive mechanical properties of the composite material are improved. The ultimate tensile strength is 254 MPa, and the Vickers hardness is 65 HV, which are 126% and 20.3% higher than those of pure zinc (112 MPa and 54 HV), respectively. The strengthening mechanisms of GNS/Zn composites are mainly load transfer of GNS and dislocation strengthening caused by coefficient of thermal expansion (CTE) mismatch. In addition, the biodegradability of GNS/Zn composites was evaluated by electrochemical measurement and immersion test. The results show that adding GNS to the zinc matrix will accelerate the degradation rate of the composite material. But the degradation rate can be controlled by the content of GNS. Its degradation rate is in the range of 69-301μm/a, an ideal degradation rate as an orthopedic implant material.